Gas jet penetration in gas-solid fluidized and jetting-fluidized beds - A review - Sauriol, Pierre; Pasikhani, Javad Vahabzadeh; Shabanian, Jaber; Chaouki, Jamal (Powder technology, 2023)
The high velocity injection of gas in a particulate system leads to the formation of a gas–solid structure characterized by enhanced momentum, mass, and heat transfers. This so-called jet structure is of great importance to many applications in gas–solid fluidized and jetting-fluidized beds. Representative applications include reactant mixing (gas–gas and/or gas–gas–solid) in homogeneous and catalyzed reactive fluidized beds, particle growth control in systems affected by deposition, and agglomeration prevention in systems with cohesive particles. The last point is especially of current interest with the development of new materials for specialized applications, such as submicron particles with typical Geldart group C behavior or processes utilizing unconventional energy feedstocks, such as crops, sludge, various waste materials, and low-grade coals. In all of these cases and many others, gas jets can be adopted as a means to optimize the operation of the fluidized or jetting-fluidized bed. It has been nearly 40 years since Massimilla wrote a review dedicated to gas jets in gas–solid fluidized beds (Massimilla, Gas Jets in Fluidized Beds, Academic Press, London, 1985). With the development of new experimental techniques and the renewed interest over the last decade, an array of new findings and correlations have recently been made accessible to the scientific community. Hence, a comprehensive review on the subject is warranted. This comprehensive review focuses on the empirical correlations developed to predict the jet penetration length and half-angle at various operating conditions in different bed configurations. In addition, a set of sensitivity analyses were performed to highlight the trends and capabilities of the selected correlations. The advances in modeling efforts and scale-up issues are also briefly reviewed. An iterative approach was further proposed to design and scale-up the injection systems in a gas–solid fluidized bed. [Display omitted] •A comparative study of empirical correlations to estimate gas jet characteristics in different fluidization conditions.•Sensitivity analyses and regime maps to highlight the trends and capabilities of screened correlations.•An overview of modeling studies on gas jet characteristics in gas-solid fluidized bed.•Design and scale-up of gas injection systems in gas-solid fluidized bed.